Pochwała Jubileuszu. O świętowaniu dwudziestopięciolecia Zakładu Literatury Staropolskiej i Polskiego Oświecenia w Uniwersytecie Rzeszowskim - Trościński, Grzegorz (Tematy i Konteksty, 2017)
The subject of the report is the jubilee of the 25th anniversary of the Department of Old Polish Literature and the Literature of Polish Enlightenment at the University of Rzeszow. The celebration took place on 14th December 2016. It gathered the authorities of the Rzeszow University, the Institute of Polish Philology, the employees of the Department and numerous guests from other scientific units of the Faculty. During the meeting occasional publication entitled Staropolskie i oświeceniowe tematy i preteksty (Old-Polish and Enlightenment topics and pre-texts). It is filled with the present employees’ of the Department works and the jubilee presentation of its output and the output of people constituting the Department in the past and at present. An occasional lecture was delivered by Professor Jerzy Jarzębski.